THE OCCURRENCE OF STROKE DISEASE IN HUMANS AND IT’S PHYSIOLOGICAL PROCESSES. (Multidisciplinary Journal of Science and Technology, 2024)
We know that by the present time, innovative technologies are developing and yet various new diseases are also developing. Various small factors are causing severe diseases. In this cited article, however, the occurrence of stroke disease in humans and the physiological processes observed in patients with this disease and changes in their psyche are cited.